Utilization of Digital Technology in Handling Schizophrenia: A Literature Study - Kurniawan Kurniawan; Sri Rahayu; Rahmah Tresnala; Toni Arisandi; Ai Indah Nazriah; Khoirunnisa Khoirunnisa; Efri Widianti; Nurlaila Fitriani (Universitas Muhammadiyah Surakarta, 2022)
In the modern era, digital technology is widely found and used by people because it is easy to access. The use of digital technology-based interventions on psychosis problems can increase cost-effectiveness because patients do not have to go to hospitals or clinics for treatment. The literature study aimed to identify the use of digital technology in the management of schizophrenia. The research method used the PICO with the keyword using in Indonesian and English